Usefulness of late gadolinium enhancement cardiac magnetic resonance to predict appropriate therapies in implantable cardioverter defibrillator patients in primary prevention. (25th November 2020) - Sanchez Somonte, P; Quinto, L; Zarakett, F; Garre, P; Alarcon, F; Tolosana, J.M; Guasch, E; Arbelo, E; Pujol, M; Caixal, G; Ortiz, J.M; Jauregui, B; et al.
Abstract: Background: The scar and the amount of border zone measured by late gadolinium enhancement cardiac magnetic resonance (LGE-CMR) has been proposed as an independent predictor of ventricular arrhythmias in patients with ischemic and non-ischemic cardiomyopathy. However, at the present time, the guidelines are based only on the ejection fraction to recommend an implantable cardioverter defibrillator (ICD) in primary prevention, and only a minority of these patients receive appropriate therapies. So, prevention needs to be improved. Purpose: To identify predictors of appropriate therapies in patients with a primary prevention ICD using cardiac magnetic resonance imaging and a dedicated software (ADAS-3D) to characterize the scar. Methods: Patients who underwent a LGE-MR prior to ICD implantation in primary prevention were retrospectively included. Clinical and cardiac imaging characteristics were collected. The myocardium was segmented with ADAS-3D software in 10 layers (from endocardium to epicardium). The scar, border zone, core and conducting channels were automatically measured in grams by the software. Results: Since 2008 to 2017, 206 patients were included. Mean age was 67±28 years, 80% men, mean ejection fraction 26%±9, 52% with ischemic cardiomyopathy and 48% non-ischemic. The primary endpoint was appropriate therapies and/or sudden cardiac death (SCD). Median follow-up was 46.33 months. 46 patients (22%) reached the primary endpoint. Greater scar mass (36.05 grams vs 21.5 grams; HR 1.04; 95% CI (1.03–1-05), p<0.001), core mass (9.8 grams vs 5.6 grams; HR 1.06; 95% CI (1.04–1-09), p<0.001), border zone mass (26.2 grams vs 15.9 grams; HR 1.05; 95% CI (1.04–1-09), p<0.001) and channel mass (3.0 grams vs 1.6 grams; HR 1.15 95% CI (1.06–1.25), p<0.001) were associated with appropriate therapies and SCD. A border zone mass >5.3 grams was independently associated with the primary endpoint (HR: 4.77; 95% CI (1.15–19.73), p=0.03). Conclusions: The amount of border zone, core and channel mass measured by LGE-MR and ADAS software are independent predictors of appropriate therapies and SCD in patients with ICD in primary prevention. Funding Acknowledgement: Type of funding source: None